'You're sicker than you think': continuing communication problems in end stage heart failure. (1st April 2011) - Mair, F S; Browne, S; Morrison, D; Macleod, U; May, C R
Abstract : Abstract: Heart failure is a terminal condition. Yet it has been demonstrated that compared to cancer, health professionals (HPs) lack confidence in diagnosing end stage heart failure (ESHF) and communicating a poor prognosis to patients. The present study seeks to explore patient and carer level of understanding of the diagnosis and prognosis, and how ESHF patients and carers make sense of their condition and plan for the future, and what part HPs play. Methods: This study involves semi-structured interviews with 22 ESHF patients and their carers and explored their knowledge and understanding of the condition and its prognosis. Qualitative data analysed using thematic analysis but informed by Normalisation Process Theory. Inclusion criteria: at least Grade 3 or 4 NYHA classification HF; who have ongoing symptoms despite optimal therapy; and have a history of admissions for this condition and their carer (defined as the person most closely involved with them). Results: Patients and carers generally understood the patient had heart problems although the term 'heart failure' was rarely used. Many patients had been unwell with heart problems for many years and the transition to ESHF remained unclear with few seeming to appreciate their prognosis. There was little evidence of direct communication about prognosis, with patients sometimes becoming fixated on comments by HPs such as, 'you're sicker than you think, you know' and wondering how to interpret such comments. Conclusions: This study has highlighted continuing problems with regard to ESHF patient and carer knowledge and understanding of their condition.